IL-18 receptor marks functional CD8+ T cells in non-small cell lung cancer. (3rd July 2017) - Timperi, Eleonora; Focaccetti, Chiara; Gallerano, Daniela; Panetta, Mariangela; Spada, Sheila; Gallo, Enzo; Visca, Paolo; Venuta, Federico; Diso, Daniele; Prelaj, Arsela; Longo, Flavia; Facciolo, Francesco; et al.
ABSTRACT: IL-18 is an inflammasome-related cytokine, member of the IL-1 family, produced by a wide range of cells in response to signals by several pathogen- or damage-associated molecular patterns. It can be highly represented in tumor patients, but its relevance in human cancer development is not clear. In this study, we provide evidence that IL-18 is principally expressed in tumor cells and, in concert with other conventional Th1 cell-driven cytokines, has a pivotal role in establishing a pro-inflammatory milieu in the tumor microenvironment of human non-small cell lung cancer (NSCLC). Interestingly, the analysis of tumor-infiltrating CD8 + T cell populations showed that (i) the relative IL-18 receptor (IL-18R) is significantly more expressed by the minority of cells with a functional phenotype (T-bet + Eomes + ), than by the majority of those with the dysfunctional phenotype T-bet − Eomes + generally resident within tumors; (ii) as a consequence, the former are significantly more responsive than the latter to IL-18 stimulus in terms of IFNγ production ex vivo ; (iii) PD-1 expression does not discriminate these two populations. These data indicate that IL-18R may represent a biomarker of the minority of functional tumor-infiltrating CD8 + T cells in adenocarcinoma NSCLC patients. In addition, our results lead to envisage the possible therapeutic usage of IL-18 in NSCLC, even in combination with other checkpoint inhibitor approaches.